British Journal of Middle Eastern Studies (jstor)
The British Journal of Middle Eastern Studies is a refereed academic journal published for the British Society for Middle Eastern Studies (popularly known as BRISMES). The editors aim to maintain a balance in the Journal's coverage between the modern social sciences and the more traditional disciplines associated with Middle Eastern and Islamic Studies.
Keywords: Middle East Studies